Improving Digital Literacy Among Elementary School Students Through Interactive Learning and Online Platforms: Embracing an Era of Flexible and Inclusive Education - Baso Intang Sappaile (PT. Anagata Sembagi Education, 2025)
The development of digital technology requires the strengthening of digital literacy from elementary school level as part of 21st century competencies. However, students' ability to access, evaluate, and produce digital information is still relatively low. This study aims to evaluate the effectiveness of interactive learning based on online platforms in improving the digital literacy of elementary school students. The study employs a descriptive qualitative approach with a case study design on fifth-grade students at a public elementary school in an urban area. Data were collected through observation, interviews, documentation, and digital literacy assessments before and after the intervention. Over three months, students participated in learning that integrated Google Classroom for task management, Wordwall for interactive evaluation, and Canva for digital content production. The results showed an average increase in students' digital literacy scores from 56 to 84, with significant improvements in information search (35%) and digital content production (42%). Students also began to demonstrate awareness of digital ethics, such as maintaining privacy and recognizing fake news. The main challenges included limitations in devices and internet connectivity, while supporting factors included school principal support, teacher readiness, and parental involvement. The study concluded that interactive learning based on online platforms is effective in improving elementary school students' digital literacy. Implications suggest that this learning model could serve as a strategic alternative to support more flexible, adaptive, and inclusive education in the digital age